Numerical simulation of sulfuric acid vapor condensation characteristics on an external three-dimensional finned tube surface. (5th November 2019) - Wang, J.L.; Tao, Y.B.; He, Ya-Ling
Highlights: A heat and mass transfer model of flue gas on finned tube surface was developed. Condensation characteristics of acid and water vapor were investigated. Distribution of acid condensation rate and solution concentration were derived. Effects of operation parameters were examined. Abstract: Three-dimensional external finned tube heat exchanger has been widely applied in waste heat recovery system. However, the current researches mainly focus on its fluid flow and heat transfer characteristics. The condensation of sulfuric acid and water vapors on heat exchanger surface, which can cause severe low temperature corrosion and reduce equipment efficiency, has rarely been reported. In this study, a heat and mass transfer model for flue gas on finned tube surface was developed to investigate the sulfuric acid and water vapor condensation characteristics and their distributions. The effects of flue gas velocity and temperature, acid and water vapor concentrations, and surface temperature were examined. The results show that the distribution of acid solution concentration on finned tube surface mostly depends on the distribution of fin surface temperature. At the windward side (especially near the minimum flow cross section region), both fin surface temperature and condensed acid solution concentration reaches the maximum value. Increasing velocity leads to vapors condensation rate and acid solution concentration increasing. The acid solution concentration decreases with flue gas temperature or tube wall temperature increasing. The present work could provide effective theoretical guidance for anti-corrosion design of finned tube heat exchanger.